Analisis Faktor-Faktor Yang Mempengaruhi Auditor Switching Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index Tahun 2011-2015 - Saputro, Anindito Dimas, Dr. Zulfikar, S.E., M.Si (2017)
This study aimed to examine the factors that affect the auditor switching. Variables that considered to affect are management changes, audit opinion, financial distress, percentage ROA, KAP size, and client size. The populations in this study are all manufacturing companies listed in Jakarta Islamic Index, period 2011-2015. The methods used to determine sample is purposive sampling. Based on those criteria, 80 companies acquired during five years of observation. Data analysis technique used is logistic regression analysis. The results ofthis research indicate that the management changes firm does not affect the auditor switching with a significance level (α) 0.997>0.05. Audit opinion does not affect the auditor switching with a significance level (α) 0.999<0.05. Firm financial distress does not affect the auditor switching with a significance level (α) 1.000>0.05. Percentage ROA affect the auditor switching with a significance level (α) 0.040<0.05. KAP size does not affect the auditor switching with a significance level (α) 0,996>0,05. Client size does not affect the auditor switching with a significance level (α) 0,381>0,5.